Cranial Cruciate Ligament Disease and Excessive Tibial Plateau Angle in Dogs:: Treatment with CBLO Technique - Costa Mancilha Dias, Luana; Augusto Lopes Muzzi, Leonardo; Munhoz Garcia Perez Neto, Daniel; Yoiti Kitamura Kawamoto, Fernando; Pimenta Neves, Mariana; Martins Araújo, Iara; de Souza Pereira, Lucas; Teixeira Naves, Júlia (Acta Scientiae Veterinariae, 2025)
Background: Cranial cruciate ligament (CCL) disease is one of the most common causes of lameness in dogs, leading to joint instability and severe progressive osteoarthritis. Some dogs have an excessively inclined tibial plateau angle (TPA) which represents a predisposing anatomical factor for CCL disease. Surgical correction is widely recommended, with tibial corrective osteotomies frequently used. Among the corrective techniques, the CORA-Based Leveling Osteotomy (CBLO) technique reduces cranial tibial thrust through a radial osteotomy centered at the CORA of the proximal tibia. The objective of this study is to report the use of the CBLO technique in 2 dogs with CCL disease and excessive TPA. Cases: Two dogs were presented to the University Veterinary Hospital for evaluation and treatment. Case 1. A 9-year-old Jack Russell weighing 10.8 kg, presenting with a 30-day history of bilateral lameness, predominantly affecting the right pelvic limb. Following clinical and radiographic examinations, a diagnosis of bilateral CCL disease was established. Case 2. A 5-year-old, mixed-breed dog weighing 11.5 kg, presented with left pelvic limb lameness after climbing stairs, which diagnostic examinations confirmed unilateral CCL disease. In both cases, radiographic examinations enabled the measurement of TPA. In the 1st dog, the TPA was measured at 35º in the right pelvic limb, while in the 2nd dog, the TPA was measured at 37º in the left pelvic limb. In both cases, these values were considered indicative of an excessive TPA. Surgical treatment using the CBLO technique was chosen and both dogs underwent the same anesthetic protocol and surgical procedure. In the 1st case, the CORA angle was calculated at 31.5°, and a bone rotation of 5.4 mm was planned to achieve an ideal postoperative TPA of approximately 10°. In the 2nd case, the CORA angle was calculated at 34°, and a bone rotation of 7.0 mm was planned to achieve an ideal postoperative TPA of approximately 10°. In the surgical procedure, medial arthrotomy was performed to allow joint inspection, which revealed lesions in the medial menisci. Partial meniscectomy was carried out, followed by capsulorrhaphy. Radial osteotomies were performed using saw blades with radii of 10 mm and 12 mm, respectively. Following cranial rotation of the proximal tibial segment, the bone segments were stabilized using pre-contoured CBLO plates (2.4 mm and 2.7 mm) and locked screws. A headless compression screw was also used to reinforce the stabilization. The muscle fasciae, subcutaneous tissue, and skin were routinely sutured. The immediate postoperative radiographs showed that final TPAs of 11° in the 1st dog and 9° in the 2nd. Postoperative care included analgesics, anti-inflammatory drugs, and antibiotics for 7 days, soft bandage for 5 days, and restricted activity for 2 months. At the 30-day postoperative reassessment, both dogs showed good weight-bearing on the operated pelvic limb, with slight lameness. On radiographic examination, the implants were well positioned, and there were signs of initial bone healing at the osteotomy site. Both dogs showed progressive improvement in limb function, with reports of complete recovery within 3 months. Discussion: In some cases of dogs with CCL disease and excessive TPA, a combination of surgical techniques may be employed in the treatment of these conditions; however, combining techniques can increase the rate of postoperative complications. The results of these 2 cases demonstrate that the only CBLO technique was effective in treating CCL disease in dogs with excessive TPA. This approach appears to be a viable option for patients with these conditions in the stifle joint and that it is possible to correct them using only 1 corrective tibial osteotomy technique. Keywords: tibial osteotomies, stifle joint, joint disease, small animals. Título: Doença do ligamento cruzado cranial e angulação excessiva do platô tibial em cães: tratamento com a Técnica de CBLO Descritores: osteotomias tibiais, articulação do joelho, doença articular, pequenos animais.